2010
DOI: 10.1021/ja100351w
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Nile Red-Based Probe for Cholesterol and Lipid Order at the Outer Leaflet of Biomembranes

Abstract: Cholesterol and sphingomyelin form together a highly ordered membrane phase, which is believed to play important biological functions in plasma membranes of mammalian cells. Since sphingomyelin is present mainly at the outer leaflet of cell membranes, monitoring its lipid order requires molecular probes capable to bind specifically at this leaflet and exhibit negligibly slow flip-flop. In the present work, such a probe was developed by modifying the solvatochromic fluorescent dye Nile Red with an amphiphilic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
456
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(497 citation statements)
references
References 100 publications
41
456
0
Order By: Relevance
“…The fluorescence of membrane dyes is influenced by the physical properties of the lipid environment (39)(40)(41)(42). Because the strongly fluorescent membrane patches cannot be explained by excess cell membrane, it is likely that they constitute a different physical membrane environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescence of membrane dyes is influenced by the physical properties of the lipid environment (39)(40)(41)(42). Because the strongly fluorescent membrane patches cannot be explained by excess cell membrane, it is likely that they constitute a different physical membrane environment.…”
Section: Resultsmentioning
confidence: 99%
“…MreB polymers organize these fluid lipids in microscopically visible regions of increased fluidity (RIFs) (38). It has been speculated that the liquid-disordered state of these RIFs attracts more membrane dye molecules and/or increases their fluorescence quantum yield, resulting in enhanced fluorescence (39). In B. subtilis, depolarization of the membrane leads to clustering of MreB polymers together with RIFs, resulting in a strong focal fluorescent signal of the membrane dye (38).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, a wide range of fluorescent probes suitable for probing multiple properties of lipid membranes was developed,13 including probes for sensing membrane potential and fluidity,14 for detecting lipid order in the outer lipid leaflet of the lipid bilayer15 and for sensing changes in the membrane during apoptosis 16. In this work, we utilized BODIPY‐C 10 17, 18 (Figure 1), a fluorophore that belongs to a group of dyes termed ‘molecular rotors’ that have viscosity‐dependent fluorescence quantum yields, lifetimes,19, 20 and depolarization 21, 22.…”
Section: Introductionmentioning
confidence: 99%
“…The mutated protein has unchanged functional properties, compared to wild-type ErbB1, and can be covalently labeled with a fluorophore at a specific serine in the acyl carrier tag. By measuring FRET between the acyl carrier tag and a novel lipid probe that localizes exclusively to the outer leaflet of the cell membrane (Kucherak et al 2010), we determined the apparent relative distance to the membrane of the ACP tag under nonactivation and activation conditions. The fluorescence lifetime imaging microscopy (FLIM) experiments showed that the unliganded receptor is situated with its amino terminus significantly closer to the membrane than after EGF addition, thereby supporting the model in which most of the inactive receptor in the plasma membane of quiescent cells is in the self-inhibited, tethered configuration (Ziomkiewicz et al 2013).…”
Section: What Is the Structure Of The Erbb1 In Living Cells?mentioning
confidence: 99%
“…Chung et al (2010) calculated from single-particle analysis of mAb (Fab) binding that there was a predominance of receptors at the periphery of the cell. Surface plasmon resonance measurements based on gold immunolabeling reported by Wang et al (2011) indicate that the density (Kucherak et al 2010). NR12S absorbs broadly from 450 to 550 with a Förster R 0 of 5.4 nm and emits at .590 nm; and (right) donor and acceptor labeled cells bathed in 1 mm ErbB1 kinase inhibitor PD153035 and exposed to 32 nm EGF (room temperature, 5 min).…”
Section: Signaling From Filopodiamentioning
confidence: 99%